2019
DOI: 10.1167/iovs.18-25405
|View full text |Cite
|
Sign up to set email alerts
|

Oral Selumetinib Does Not Negatively Impact Photoreceptor Survival in Murine Experimental Retinal Detachment

Abstract: PurposeMitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK) signaling is neuroprotective in some retinal damage models but its role in neuronal survival during retinal detachment (RD) is unclear. In addition, serous RDs are a prevalent side effect of MEK inhibitors (MEKi), blocking MAPK/ERK signaling for treatment of certain cancers. We tested the hypothesis that MEKi treatment in experimental RD would increase photoreceptor death.MethodsThe MEKi selumetinib was delivered daily to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In the retina, MAPKs regulate apoptosis during retinal development 35 . The activation of the MAPK cascade has been shown to be especially important in Müller glial cells formation during retina development 36 and retinal detachment 37 , 38 , MAPK cascade has also been suggested to have indirect neuroprotective action for the photoreceptors in RD 39 . Interestingly, many of the identified signaling proteins were associated with proteasome-mediated protein degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In the retina, MAPKs regulate apoptosis during retinal development 35 . The activation of the MAPK cascade has been shown to be especially important in Müller glial cells formation during retina development 36 and retinal detachment 37 , 38 , MAPK cascade has also been suggested to have indirect neuroprotective action for the photoreceptors in RD 39 . Interestingly, many of the identified signaling proteins were associated with proteasome-mediated protein degradation.…”
Section: Discussionmentioning
confidence: 99%
“…A study with retinal detachment (RD) mouse model showed that selumetinib prevented the increase in phosphorylated ERK in Müller glial cells, whereas it did not block the Müller reactive signals and photoreceptor death induced by RD [ 101 ]. The treatment also blocked the increase in the number of Iba1-positive cells promoted by RD.…”
Section: Drugs and Medicinementioning
confidence: 99%
“…Because of its highly reactive property, potential therapeutic agents with an anti-oxidative activity, including curcumin and caffeic acid, have been reported to reduce acrolein-induced oxidative injuries and cell death in vitro 6 , 19 , 23 . Furthermore, oral administration of baicalein and crocin via anti-oxidative mechanisms attenuated acrolein-induced neurotoxicity in Parkinsonian and Alzheimer’s animal models, respectively 29 , 30 . In the present study, we targeted the MEK–ERK signaling pathway in acrolein-induced neurotoxicity but not PIK3-AKT signaling pathway because acrolein did not consistently alter AKT signaling 6 , 23 .…”
Section: Discussionmentioning
confidence: 98%
“…Thirdly, in addition to the present study, our previous study has reported that selumetinib significantly inhibited acrolein-induced inflammasome formation and activation of BV-2 cells, an alternative model for primary cultured microglia 9 . Due to its moderate permeability of the blood brain barrier 31 and demonstrated safety when administered orally for 14 days 30 , a systemic application of selumetinib may be beneficial to patients with acute stroke stage and SCI via inhibiting both acrolein-induced toxicity to neurons and acrolein-induced neuroinflammation in microglia as well. Currently, an in vivo study focusing on the neuroprotective effect of oral administration of Zorifertinib (an epidermal growth factor receptor-tyrosine kinase inhibitor) is ongoing to demonstrate the application of cancer target therapy for acute brain damages.…”
Section: Discussionmentioning
confidence: 99%